The role of nutrient solutions on Phosphate-solubilizing bacteria population, Phosphorus availability, Phosphorus uptake, growth and yield of Red Chili (Capsicum annuum L.) - Fitriatin, Betty Natalie; Ghifari, Raden Faqih Hilmiy; Sofyan, Emma Trinurani; Widiantini, Fitri; Fakhrurroja, Hanif; Simarmata, Tualar (Universitas Padjadjaran, 2024)
Red chili consumption in Indonesia has increased every year. However, with large chili production to meet large consumption, land conversion for various purposes has reduced the harvested area. The efforts to increase the harvested area of chili using Inceptisols soil by providing nutrient solutions to overcome the infertility of the soil using its nutrients. This experiment aims to determine the effect of nutrient solution application on the population of phosphate-solubilizing bacteria, phosphorus availability, phosphorus uptake, growth, and yield of Red Chili (Capsicum annuum L.) in Inceptisols. The experiment was conducted from August 2023 to February 2024 at Ciparanje Experimental Field, Faculty of Agriculture, Padjadjaran University, and the analysis process was conducted at the Laboratory of Soil Biology and Soil Chemistry and Plant Nutrition, Department of Soil Science and Land Resources, Faculty of Agriculture, Universitas Padjadjaran., using a factorial randomized block design with two factors, nutrient solutions concentrates (1200, 1600, 2000 ppm) and nutrient solutions doses (200, 400, 600 mL), resulting in nine treatments and three replications. The results showed that the treatment of nutrient solution concentration and dose increased the number of fruits per plant, fruit weight per plant, and yield of chili with grade A. Treatment with 2000 ppm concentrate + 600 mL dose gave the best results on the number of fruits per plant (44.7 fruits), fruit weight per plant (725g), and grade A chili yield (73 fruits).